Analisa dan Implementasi Sistem Keamanan Router Mikrotik dari Serangan Winbox Exploitation, Brute-Force, DoS - Haeruddin Haeruddin (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The advancement of technology development makes it easier to find and share any information using computer networks. Computer networks have been widely applied in homes and offices. The ease of exchanging data on the network makes the availability of computer networks and information security are vulnerable to attacks by threats. On a computer network, the device which has the vulnerability is a router. A router is the outermost device that connects the Local Area Network (LAN) to the internet so that it can be easily attacked by irresponsible parties. The Mikrotik router is a product that is widely used as a gateway router that connects LANs and the Internet. There are so many tools that can be used to carry out attacks on Mikrotik routers such as Hping3 (DoS), Hydra (Brute-Force), and Exploitation Script (Winbox Exploitation). To find out the security loop in Mikrotik routers, this study uses penetration testing methods and attack techniques such as Winbox Exploit, Brute-force, and DoS. After knowing the security gap, the next step is to provide and implementation recommendations so that similar attacks do not occur any more in the future.